The paths to autonomy: plurinational reform and indigenous governance in contemporary Bolivia. Issue 4 (2nd October 2021) - Doyle, Matthew
ABSTRACT: In Bolivia, national reforms of the Movement Towards Socialism (MAS) government, which purport to devolve power to indigenous communities, generated disagreement among the local authorities of the highland indigenous community of Bolívar province. This paper examines why this conflict occurred and how it illustrates some of the paradoxical consequences of the MAS' project of 'plurinational' reform. This situation can be explained through understanding the legacy of administrative and territorial reforms of Bolivia's 'neoliberal' period and how these have shaped the local system of government and the perspectives of its leaders.